Teaching technology: From knowing to feeling enhancing emotional and content acquisition performance through Gardner's Multiple Intelligences Theory in technology and design lessons - Jesus Sanchez-Martin; Garcia J. Alvarez-Gragera; Maria Antonia Davila-Acedo; Vicente Mellado (OmniaScience, 2017)
Gardner's Multiple Intelligences Theory (MIT) can be a cognitive and emotional improvement if is taken into account in the standard development of the Technology lessons. This work presents a preliminary evaluation of the performance enhancement in two concomitant aspects: contents acquisition and emotional yield. The study was made on up to 150 students with ages of 12-13 years old. The control group was submitted to traditional transmission-reception lessons, whereas the experimental one was submitted to novel educational techniques that included specific activities which took into account the different intelligences styles (IS) inside the classroom. The results clearly depicted that both studied variables underwent a statistical significant enhancement through the application of the MIT-based educational method.